Novelty Cosmetic Filters Based on Nanomaterials Composed of Titanium Dioxide Nanoparticles - Marta Bartoszewska; Elżbieta Adamska; Agata Kowalska; Beata Grobelna (Molecules, 2023)
The following work describes the synthesis of new physical filters based on TiO2/SiO2 and TiO2/Ag nanostructures. Titanium dioxide nanoparticles (TiO2 NPs) were applied as control material and a popular physical UV filter. The advantage of using materials on the nanometer scale is the elimination of the skin whitening effect that occurs when using photoprotective cosmetics containing titanium dioxide on a macro scale. In addition, the silica coating makes the material less harmful, and the silver coating enriches the material with antibacterial properties. Nanoparticles and nanostructures have been characterized by Energy Dispersive X-Ray Analysis (EDX), the Scanning Electron Microscope (SEM), Transmission Electron Microscopy (TEM), and Fourier-Transform Infrared Spectroscopy (FT-IR) methods. Due to the use of physical filters in anti-radiation protection cosmetics, water-in-oil (W/O) emulsion has been prepared. All cosmetic formulations have been tested for stability. The sun protection research with the Sun Protection Diagnostic SP37 was carried out. These studies made it possible to determine the natural sun protection time and to compare the synthesized materials. Furthermore, one of the most important parameters when describing this type of cosmetic is water resistance, which has also been measured. The results show that the new type of material of TiO2/Ag used as a new physical filter in emulsion W/O shows the best sun protection compared with other obtained nanomaterials. It is most likely due to the improved optical properties of the combination of noble metals, for example, silver with TiO2.